Genome-wide profiling of miRNA-gene regulatory networks in mouse postnatal heart development—implications for cardiac regeneration - Chaudhari, Umesh; Pohjolainen, Lotta; Ruskoaho, Heikki; Talman, Virpi (Frontiers in Cardiovascular Medicine, 2023)
Background After birth, mammalian cardiomyocytes substantially lose proliferative capacity with a concomitant switch from glycolytic to oxidative mitochondrial energy metabolism. Micro-RNAs (miRNAs) regulate gene expression and thus control various cellular processes. Their roles in the postnatal loss of cardiac regeneration are however still largely unclear. Here, we aimed to identify miRNA-gene regulatory networks in the neonatal heart to uncover role of miRNAs in regulation of cell cycle and metabolism. Methods and results We performed global miRNA expression profiling using total RNA extracted from mouse ventricular tissue samples collected on postnatal day 1 (P01), P04, P09, and P23. We used the miRWalk database to predict the potential target genes of differentially expressed miRNAs and our previously published mRNA transcriptomics data to identify verified target genes that showed a concomitant differential expression in the neonatal heart. We then analyzed the biological functions of the identified miRNA-gene regulatory networks using enriched Gene Ontology (GO) and KEGG pathway analyses. Altogether 46 miRNAs were differentially expressed in the distinct stages of neonatal heart development. For twenty miRNAs, up- or downregulation took place within the first 9 postnatal days thus correlating temporally with the loss of cardiac regeneration. Importantly, for several miRNAs, including miR-150-5p, miR-484, and miR-210-3p there are no previous reports about their role in cardiac development or disease. The miRNA-gene regulatory networks of upregulated miRNAs negatively regulated biological processes and KEGG pathways related to cell proliferation, while downregulated miRNAs positively regulated biological processes and KEGG pathways associated with activation of mitochondrial metabolism and developmental hypertrophic growth. Conclusion This study reports miRNAs and miRNA-gene regulatory networks with no previously described role in cardiac development or disease. These findings may help in elucidating regulatory mechanism of cardiac regeneration and in the development of regenerative therapies.